The Correlation Between Sarcopenia and Metabolic Syndrome in Elderly Patients At The Geriatric Outpatient Clinic of Wangaya Regional General Hospital in Denpasar - Setyawan, Moses Kharisma; Gautami, Gautami; Kuswardhani, R.A Tuty (Jurnal Indonesia Sosial Sains, 2026)
This is an observational study with a retrospective approach conducted using medical record data from geriatric polyclinic patients at Wangaya Hospital from December 2025 to February 2026. Samples were obtained using the total sampling method from medical records. This study included patients over 65 years of age who had measurements of weight, height, SARC-F value, and hand grip strength. The diagnosis of sarcopenia and its components (high SARC-F, low hand grip strength, low muscle mass index, and sarcopenia) were associated with the incidence of metabolic syndrome. Data are presented as numerical values, percentages, and prevalence ratio (PR) accompanied by a 95% confidence interval (CI). Statistical testing was performed using the Fisher Exact Test, with significance set at P < 0.05. Bivariate analysis was conducted to examine the association of each component with metabolic syndrome. The results show that hand grip strength (PR 0.55, CI 0.14–1.01, P = 0.05) has an almost significant relationship, and low muscle mass index (PR 0.55, CI 0.08–0.91, P = 0.04) has a significant relationship with metabolic syndrome. Other components, such as SARC-F score (PR 0.55, CI 0.13–1.20, P = 0.10) and sarcopenia (PR 0.48, CI 0.07–1.79, P = 0.28), did not show a significant association with metabolic syndrome. The findings are not conclusive. Further research is recommended using a larger sample size and standard reference methods such as dual-energy X-ray absorptiometry (DXA), bioelectrical impedance analysis (BIA), computed tomography (CT), or magnetic resonance imaging (MRI) to calculate muscle mass.